UMPSA to establish first Graduate School in Malaysia’s TVET Ecosystem - Mimi Rabita, Abd Wahit (UMPSA, 2024)
PEKAN, 20 December 2024 – Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) will soon establish the Graduate Engineering & Technological Business School (GET-BS), making it the first graduate school in Malaysia based on the TVET ecosystem.